A review of recent advancements in the impact response of fiber metal laminates - Vijayan Muniyan; Vishnu Vijay Kumar; Indran Suyambulingam; Suganya Priyadharshini; Divya Divakaran; Sanjay Mavinkere Rangappa; Suchart Siengchin (Heliyon)
Fiber metal laminates (FMLs) have garnered significant attention due to their exceptional impact resistance, making them attractive for various structural applications. This review presents recent advancements in understanding the impact behavior of FMLs under low- and high-velocity impact scenarios. Low-velocity impacts, commonly encountered during manufacturing, handling, and tool drops, are discussed, with a focus on damage mechanisms, energy absorption capabilities, and influential factors such as impactor geometry and boundary conditions. Additionally, this review delves into high-velocity impact events, simulating scenarios such as ballistic impacts, highlighting the role of FMLs in mitigating perforation and enhancing damage tolerance. The effects of various parameters on the impact response are critically analyzed. The findings presented herein contribute to the development of lightweight, impact-resistant FML components for aerospace, automotive, and defence applications.